Draft Annual Plan 2000-2001 Union Territory of Dadra & Nagar Haveli - Planning Commission (Planning Commission, 2000)
The Internal Work Study Unit of Ministry of Agriculture has also suggested to abolish the below mentioned posts & recommended their upgradation for new creation in the Department of Agriculture.
Union Territory of Dadra & Nagar Haveli, Department of Planning and Statistics